Effects of natural and artificial ripening agent on musa paradisiaca / Nurul Nadia Abdul Jalil - Abdul Jalil, Nurul Nadia (2018)
Fruit ripening is the last stage of fruit development. During the ripening process, plant hormone called ethylene will be released. The hormone ethylene initiates the ripening response such as conversion of starch to sugar, degradation of pectin and degradation of chlorophyll. However, there are an alternative sources of ethylene. The reaction of calcium carbide with water will produce acetylene gas where this gas can substitute ethylene for ripening. Calcium carbide is commonly used as artificial ripening agent but it is detrimental to health. Moreover, ripe fruits that release large amount of ethylene has the potential to become the natural ripening agent which is another alternative source of ethylene. This study aims to study the potential of pear as natural ripening agent and to compare the effects of both natural and artificial ripening agents on Musa paradisiaca (banana). DNS assay method was used to determine the glucose concentration that corresponding with ripening process. As for the peel colour development, the L*, a* and b* values were measured. In order to evaluate the firmness, force needed to penetrate the banana was measured. In this study, there is no significant difference in the rate of ripening between all three treatment groups which are control group, natural ripening agent treatment group and artificial ripening agent treatment group. This result may be due to the species of banana used where it is from the plantain group that took longer time to fully ripen therefore it did not exhibit the ripening characteristics since the experiment was only conducted up to 5 days. The type of fruit used as natural ripening agent may not release a sufficient amount of ethylene to help ripen the banana.